2021
DOI: 10.1029/2021gl094395
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Composition and Origins of Ultrafine Aerosol in the Summertime High Arctic

Abstract: Aerosol-cloud interactions have a significant effect on the energy budget of the summertime high Arctic (north of 80°). During the sunlit summer months, low clouds have a net warming effect on the atmospheric boundary layer (Tjernström et al., 2012). In cloud-free conditions, surface air temperatures are typically lower by several degrees. Isentropic atmospheric transport to the summertime high Arctic is limited by "domes" of low constant potential temperature, particularly at lower elevations (Klonecki et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 74 publications
2
32
0
Order By: Relevance
“…Based on the adiabatic parcel model simulations performed, this would require initializing the model with a characteristic updraft velocity of around 0.5–0.6 m s −1 (Figure S16b in Supporting Information S1 ). From the simulations we demonstrate activation of particles down to around 25 nm diameter at updraft velocities of 1 m s −1 for particles consisting of 30% ammonium sulfate and 70% organics (a compromise between the composition in Figure 4a and the Aitken mode chemical composition in Lawler et al., 2021 , cf. below).…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…Based on the adiabatic parcel model simulations performed, this would require initializing the model with a characteristic updraft velocity of around 0.5–0.6 m s −1 (Figure S16b in Supporting Information S1 ). From the simulations we demonstrate activation of particles down to around 25 nm diameter at updraft velocities of 1 m s −1 for particles consisting of 30% ammonium sulfate and 70% organics (a compromise between the composition in Figure 4a and the Aitken mode chemical composition in Lawler et al., 2021 , cf. below).…”
Section: Resultsmentioning
confidence: 78%
“…As far as the Aitken mode is concerned, Lawler et al. ( 2021 ) determined the mean Aitken mode composition during fog periods (during AO18) to include at least 25% organics such as secondary organic aerosol and polysaccharides, while another 25% consisted of inorganic compounds (mostly sulfate). Approximately half of the mass was not determined in Lawler et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Laminaria kelp species are present in this upwelling system, and they are known for their iodine bioaccumulation and reactive iodine release (McFiggans et al., 2004; Velimirov et al., 1977). In addition, a previous study in the High Arctic, where iodic acid plays a major role in NPF, showed that particle growth was driven by other species, for example, organics (Lawler et al., 2021). Consequently, with the data at hand, we cannot discriminate between these two competing hypotheses (i.e., iodine vs. sulfuric acid triggered nucleation).…”
Section: Resultsmentioning
confidence: 99%